Management not models: adaptability, responsiveness, and a few lessons from football - and Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.